2012
DOI: 10.1523/jneurosci.0114-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoids in Amygdala and Nucleus Accumbens Mediate Social Play Reward in Adolescent Rats

Abstract: The brain endocannabinoid system plays a crucial role in emotional processes. We have previously identified an important role for endocannabinoids in social play behavior, a highly rewarding form of social interaction in adolescent rats. Here, we tested the hypothesis that endocannabinoid modulation of social play behavior occurs in brain regions implicated in emotion and motivation. Social play increased levels of the endocannabinoid anandamide in the amygdala and nucleus accumbens (NAc), but not in prefronta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
169
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(183 citation statements)
references
References 77 publications
(151 reference statements)
6
169
0
5
Order By: Relevance
“…As CB 1 receptors are predominantly expressed on CCK þ terminals (Marsicano and Lutz, 1999;Ramikie and Patel, 2011), and CB 1 activation produces a selective inhibition of these cells (Hentges et al, 2005), we postulated that endocannabinoid-induced inhibition of CCK þ interneurons is lost/reduced in PCP-treated rats, thus resulting in social withdrawal (Supplementary Figure S7). In support of this hypothesis, our study and other reports have shown increased AEA (Trezza et al, 2012) and decreased CCK levels (Panksepp et al, 2004) during social interaction in normal rats. In PCP-treated rats, which are characterized by deficient AEA mobilization, endocannabinoid elevation back to control levels, or direct activation of CB 1 receptors or blockade of CCK2 receptors, reverses the social behavior deficit.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As CB 1 receptors are predominantly expressed on CCK þ terminals (Marsicano and Lutz, 1999;Ramikie and Patel, 2011), and CB 1 activation produces a selective inhibition of these cells (Hentges et al, 2005), we postulated that endocannabinoid-induced inhibition of CCK þ interneurons is lost/reduced in PCP-treated rats, thus resulting in social withdrawal (Supplementary Figure S7). In support of this hypothesis, our study and other reports have shown increased AEA (Trezza et al, 2012) and decreased CCK levels (Panksepp et al, 2004) during social interaction in normal rats. In PCP-treated rats, which are characterized by deficient AEA mobilization, endocannabinoid elevation back to control levels, or direct activation of CB 1 receptors or blockade of CCK2 receptors, reverses the social behavior deficit.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, we found that the 'on demand' production of AEA occurring during social interaction (Trezza et al, 2012) is significantly reduced in PCP-treated rats in brain areas relevant to social behavior, such as the mPFC and amygdala. The resulting deficient CB 1 activation cannot be attributed to decreased CB 1 expression, nor to disrupted CB 1 function/coupling, as neither one are affected in our animal model (Seillier et al, 2010).…”
Section: Discussionmentioning
confidence: 80%
“…In humans, marijuana can either facilitate or impair social interactions and social saliency, possibly depending on dose and context (1-3). Analogously, in animal models, cannabinoid receptor activation with direct-acting agonist drugs disrupts social interactions, whereas FAAH inhibition enhances them, which is suggestive of a role for anandamide in socialization (9,25,26). Although important, these data leave unanswered two key questions.…”
Section: Discussionmentioning
confidence: 95%
“…Consistent with this idea, CB 1 receptors are highly expressed in associational cortical regions of the frontal lobe and subcortical structures that underpin human social-emotional functioning (6,7). Moreover, the receptors and their endogenous lipid-derived ligands, anandamide and 2-arachidonoyl-sn-glycerol (2-AG) (8), have been implicated in the control of social play (9) and social anxiety (10,11), two crucial aspects of the social experience. Another essential facet of social behavior, the adaptive reinforcement of interactions among members of a group (i.e., the reward of being social), requires the oxytocin-dependent induction of long-term synaptic plasticity at excitatory synapses of the nucleus accumbens (NAc) (12), a key region in the brain reward circuit.…”
mentioning
confidence: 99%
“…Previous studies have shown that the nucleus accumbens (NAc), a brain region widely implicated in reward and motivation (Berridge and Kringelbach, 2008;Everitt and Robbins, 2005;Floresco, 2015), modulates the positive subjective properties of social play behavior in rats (Gordon et al, 2002;Trezza et al, 2011Trezza et al, , 2012van Kerkhof et al, 2013van Kerkhof et al, , 2014Vanderschuren et al, 1995b). Interestingly, peer-peer interactions in 4-week-old rats increase dopamine activity in the NAc (Robinson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%